Multifocal Avian Influenza (H5N1) Outbreak - Balicer, Ran D.; Reznikovich, Shmuel; Berman, Elyakum; Pirak, Michael; Inbar, Amnon; Pokamunski, Shimon; Grotto, Itamar (Emerging infectious diseases, 2007)
During March 2006, an outbreak of highly pathogenic avian influenza (H5N1) occurred in multiple poultry farms in Israel. The epidemiologic investigation and review of outbreak mitigation efforts uncovered gaps in planning for and containing the outbreak, thus affording valuable lessons applicable to other countries in similar settings.